Saluran Pemasaran Kopi yang Efisien di Kecamatan Karanglewas Kabupaten Banyumas - Barokatuminalloh Barokatuminalloh; Neni Widayaningsih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
The research aim is to seek the pattern of coffee marketing, operational efficiency of coffee marketing in Karanglewas District Banyumas Regency. The result of the research found three pattern of coffe marketing process in Karanglewas District Banyumas Regency involving farmers, wholesalers, out of town sellers, food processors and retailers. Operationally pattern I which is: farmers – Wholesalers - Retailers, is the most efficient marketing strategy compare with another marketing strategy. Actually, the biggest percentage of farmer’s share at pattern II, but because of limitation researcher, if this pattern more investigated then possibility there will found longest marketing channel. Price correlation between producer market and consumer market is close enough which is 0,956 with determinan coefficient 0,9139 and elasticity of price transmission in producer market and consumer market is 0,3665. Based on coefficient of price correlation and elasticity of price transmission then price efficiency was not achieved yet. Based on the research summarize that operational efficiency of marketing channel coffe is efficient. It is shown by farmer’s share analysis which is convected with the percentage of marketing margin in every marketing pattern. Keywords: marketing channel, farmer’s share, marketing margin